Using wikis for effective peer assessment - Quartermaine, Lynne; O’Hare, Sheena; Cooke, Audrey (Curtin University, 2012)
In 2009, Curtin University began offering a Bachelor of Education (Primary) program fully online apart from practicum school placements. At Curtin, the Bachelor of Education course has the same structure and units regardless of whether it is taught on campus, regionally or online. The units match in content and assessment and all use Blackboard as the Learning Management System (LMS). For online students, the LMS is the sole source of unit information, documentation submission of assessments and interactions between the students, the teachers and the content and considerable thought has been given to assisting student development in the use of technology and optimising the likelihood of active engagement. Contrary to initial expectations, not all students were technologically sophisticated. Indeed many students were tentative—frightened that they would break something—and generally nervous about learning technologies. To engage students in the learning process, the decision was made to incorporate a wiki, TypeWithMe, into the group assignment. It was hoped that the wiki would benefit students in their group work and the peer assessments aspect of one of their assessments. The results indicated that even though students had concerns regarding their technological ability, they reported that TypeWithMe was easy to use and assisted in both their group work and peer assessment.